A MEASLES OUTBREAK. IS THE THREAT REAL? - Inga V. Artemova; Tatiana V. Kulichenko (Вопросы современной педиатрии, 2017)
Measles is a well-studied manageable disease. Vaccination resulted in a significant reduction in the incidence of this infection. However, more recently, measles outbreaks have become more frequent in countries where it would seem there was one step left before the complete virus elimination. The article provides basic information about the measles agent, clinical manifestations, and preventive measures. The causes of new measles outbreaks in developed countries are discussed.